Association of Primary Caretaker's Dental Caries and Socioeconomic Status with the Pattern and Severity of Early Childhood Caries in their Children - Amina Sultan; Akanksha Juneja; Panchali Batra; Sakshi Katyal (Journal of South Asian Association of Pediatric Dentistry)
Background: Dental caries in preschoolers, also known as early childhood caries (ECC), is significantly associated with socioeconomic conditions, oral hygiene practices, parental beliefs and educational status, maternal nutrition, and psychosocial factors. Mothers play a significant role in their children's care, as they are more likely responsible for their children's upbringing compared to fathers. Also, young children often spend most of their time with their mothers, including at preschools. This means that mothers’ education, financial status, occupation, and oral health practices can significantly impact their children's oral health. This study hypothesizes that mothers’ socioeconomic position and dental caries status are significantly linked to ECC in their children. Aim: To assess the primary caretaker's dental caries status and their socioeconomic status (SES) as possible risk factors for the presence of ECC in their children. Materials and methods: Mothers were selected as primary caregivers, due to their significant role in their children's care, as they are more likely responsible for their children's upbringing compared to fathers. This questionnaire-based survey was carried out on 100 children–mother pairs. The modified Kuppuswamy scale was used to assess the demographic details and SES of the primary caretaker. The dental caries experience of the patient and the primary caretaker were recorded using the World Health Organization (WHO) Oral Health Assessment criteria. Correlation and regression analysis was used. The level of statistical significance was kept at p < 0.05. Results: Child participants had a mean deft of 5.1 ± 3.7 [mean decayed teeth (DT) 4.18 ± 2.7; mean filled teeth (FT) 0.35 ± 0.8]. In total, 65% of children with ECC had dmft below 6 and 35% of children with ECC had either dmft 6 or above. Mean DMFT of the primary caregiver (mothers) was 2.17 ± 2.4. A statistically significant relationship between the SES of the mother and the deft of the child was observed (p < 0.05). In total, 2.5% of the variability in deft (child) was predicted by SES. Conclusion: Primary caregiver decayed, missing, and filled surfaces (DMFSs) scores and SES are significant indicators for the ECC. Clinical significance: Early childhood caries in children are significantly associated with maternal variables, including maternal dental caries status and oral hygiene level. Pediatric dentists should consider dental caries in the mother as a risk factor for caries activity in their children.